Selective synthesis of acetonitrile by reaction of ethanol with ammonia over Ni/Al2O3 catalyst - Jeong, Ye-Seul; An, Sang Hee; Shin, Chae-Ho (The Korean journal of chemical engineering, 2019)
A highly selective synthesis of acetonitrile was carried out by the reaction of ethanol with ammonia on a 10 wt% Ni/Al 2 O 3 catalyst. The conversion of ethanol and selectivity to acetonitrile, ethylene, and monoethylamine were examined by varying experimental parameters such as ammonia partial pressure, reaction temperature, and space time. The increase in the ammonia partial pressure led to a considerable decrease in the conversion and small increase in the acetonitrile selectivity up to a molar ratio of NH 3 /ethanol of 3, followed by almost constant values. The partial reaction order of ethanol obtained by controlling the space time was one, while that of ammonia was negative, −0.4. The deactivation behavior of the catalyst after 100 h on stream reaction at 230 °C was analyzed by X-ray photoelectron spectroscopy and temperature programmed oxidation of the catalyst used. The catalyst deactivation was attributed to the gradual formation of nickel carbonitride on the catalyst surface.